Preparation method of high-performance water-based acrylic acid-based soft ceramic chip super-hydrophobic coating material
By preparing high-performance water-based acrylic-based soft ceramic sheet superhydrophobic coating materials, the corrosion and cracking problems of soft ceramic sheets in outdoor environments are solved, excellent hydrophobicity and weather resistance are achieved, and the service life and decorative performance of soft ceramic sheets are improved.
Patent Information
- Application Number
- CN202510905702.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-08-01
- Estimated Expiration
- 2045-07-01
AI Technical Summary
Existing soft porcelain pieces face complex and changeable environments in outdoor building decoration, and are susceptible to surface cracking of materials caused by rainwater acid and alkali corrosion and humidity changes, which affect their performance and life.
The preparation method of high-performance aqueous acrylic-based soft ceramic sheet superhydrophobic coating material is adopted. By modifying silica particles and combining them with composite resins composed of acrylic resin, polyurethane, cellulose nanocrystals and epoxy resins, a nano-enhanced network structure is formed to enhance the hydrophobicity, wear resistance and crack resistance of the coating.
The prepared coating material has excellent hydrophobic properties, acid and alkali resistance, high and low temperature resistance and self-cleaning ability, which significantly improves the weather resistance and service life of soft ceramic sheets, and is suitable for protective coatings of outdoor decoration materials.
Smart Images

Figure CN120399550A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of hydrophobic coating material preparation, and particularly relates to a preparation method of a high-performance waterborne acrylic-based soft porcelain sheet superhydrophobic coating material. Background Art
[0002] The soft porcelain sheets produced by the prior art are undoubtedly a new type of building decoration material leading the trend, which combines the concept of environmental protection and technological innovation. The preparation of this material mainly relies on a series of carefully selected raw materials, including finely processed construction waste and industrial waste residues, which were originally regarded as burdens but are given new life here; specially modified clay, which endows the soft porcelain sheets with unique physical properties; and selected quartz sand and calcium carbonate powders, etc. They are skillfully mixed with a certain proportion of adhesives, and through precise proportioning and process control, the uniformity and stability of the material are ensured. These raw materials undergo a complex process of low-temperature baking and radiation cross-linking in a special temperature-controlled shaping system, and finally form a building decoration material that is both environmentally friendly and low-carbon and has excellent flexibility.
[0003] Compared with traditional hard ceramics, the advantages of soft porcelain sheets are obvious. Its material is lighter and thinner, which greatly reduces the overall weight of the product. This not only facilitates the loading and unloading during transportation but also simplifies the installation process, reducing the construction difficulty and cost. At the same time, the soft porcelain sheets show remarkable impact resistance. Even when facing accidental impacts or external forces, they are not easily broken, which significantly improves the durability and service life of the product and provides users with a more lasting and stable decorative effect.
[0004] However, when soft porcelain sheets are applied to the field of outdoor building decoration, the challenges they face also follow. The natural environment is complex and changeable. Soft porcelain sheets not only have to withstand the baptism of strong winds and heavy rains but also face the corrosive effects of acid and alkali components in rainwater. More complicatedly, with the change of environmental humidity, soft porcelain sheets may show the phenomenon of moisture absorption and expansion or dehydration and contraction. This repeated volume change is extremely likely to cause cracks on the material surface, thus seriously affecting the overall performance and life of the soft porcelain sheets. Therefore, how to improve its adaptability to the external environment while maintaining the original advantages of soft porcelain sheets has become an urgent problem to be solved.
[0005] In this context, the superhydrophobic coating material applied on the soft porcelain tiles is particularly important. This coating is like an invisible shield that can effectively isolate the erosion of moisture, acids, and alkalis, protecting the soft porcelain tiles from damage. Currently, in the field of superhydrophobic material research, polymer nanocomposite superhydrophobic materials have attracted much attention due to their unique properties. These materials embed inorganic nano-particles in various forms into the polymer matrix in a highly dispersed and filled manner, forming a superhydrophobic composite material with a dense structure and excellent performance. This composite material not only has excellent hydrophobic properties but also can improve the wear resistance, weather resistance, and self-cleaning ability of the soft porcelain tiles to a certain extent, providing a more solid guarantee for the application of soft porcelain tiles in the field of outdoor building decoration. Summary of the Invention
[0006] The present invention provides a preparation method for a high-performance waterborne acrylic-based superhydrophobic coating material for soft porcelain tiles, which has excellent properties and can meet the application in the decoration field.
[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions:
[0008] A preparation method for a high-performance waterborne acrylic-based superhydrophobic coating material for soft porcelain tiles, comprising the following steps:
[0009] (1) Put the glass slide into a beaker filled with absolute ethanol for ultrasonic cleaning, and then put the cleaned glass slide into an oven for drying for later use;
[0010] (2) Place the silicon dioxide particles in a beaker, add absolute ethanol to the beaker, stir, and then place it in an ultrasonic vibration cleaning machine to disperse them evenly. Then, add FAS-17 (1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane) dropwise to the beaker, and place it in a water bath for stirring until all the absolute ethanol has evaporated, and then cool to obtain the modified silicon dioxide for standby;
[0011] (3) Add acrylic resin, polyurethane, and absolute ethanol to a beaker, and then stir under water bath conditions. Add the modified silicon dioxide to the beaker, and then stir under water bath conditions. Then, add γ-aminopropyltriethoxysilane, cellulose nanocrystals, and epoxy resin to it, and then stir under water bath conditions and cool to room temperature;
[0012] (4) Coat the coating on the glass slide by the coating method, and cure it at room temperature to obtain a high-performance waterborne acrylic-based superhydrophobic coating material for soft porcelain tiles.
[0013] Preferably, in step (1), the time for putting the glass slide into a beaker filled with absolute ethanol for ultrasonic cleaning is 10-15 minutes.
[0014] Preferably, after stirring for 15 min in step (2), it is placed in an ultrasonic vibration cleaning machine.
[0015] Preferably, after stirring in step (2), it is placed in an ultrasonic vibration cleaning machine and dispersed for 10 - 15 min to make it evenly dispersed.
[0016] Preferably, in step (3), acrylic resin, polyurethane and absolute ethanol are added into a beaker and stirred for 1 h under the water bath condition of 35 - 40 °C.
[0017] Preferably, the modified silica is added into a beaker in step (3) and stirred for 30 min under the water bath condition of 35 - 40 °C.
[0018] Preferably, γ - aminopropyltriethoxysilane, cellulose nanocrystals and epoxy resin are added thereto in step (3), stirred for 30 - 35 min under the water bath condition of 35 - 40 °C, and then cooled to room temperature.
[0019] Preferably, the curing time at room temperature in step (4) is 10 - 15 min.
[0020] The preparation technical principle of the high - performance water - borne acrylic - based soft porcelain chip super - hydrophobic coating material of the present invention:
[0021] I. Specific functions of raw materials
[0022] 1. Glass slide
[0023] The glass slide serves as the bearing substrate of the coating throughout the preparation process. It provides a flat and clean surface for the subsequent coating application, enabling the coating to adhere evenly thereon, facilitating the observation and testing of the coating performance.
[0024] 2. Silica particles
[0025] Silica particles are the key raw materials for constructing the microscopic structure of the super - hydrophobic coating surface. Nano - scale silica particles have a large specific surface area, which can form microscopic roughness on the coating surface. This roughness is one of the important factors for achieving super - hydrophobic performance. It can increase the contact angle between water and the coating surface, cause water to form water droplets and roll on the coating surface, thereby taking away pollutants such as dust on the surface and realizing the self - cleaning function. At the same time, silica particles can also enhance the strength and toughness of the coating material and improve the wear resistance of the coating.
[0026] 3. FAS - 17 (1H, 1H, 2H, 2H - perfluorodecyltriethoxysilane)
[0027] FAS-17 is mainly used for surface modification of silica particles. It has extremely low surface energy and can combine with the hydroxyl groups on the surface of silica particles through chemical reactions to form a fluorocarbon chain with low surface energy on the surface of silica particles. The silica particles modified by FAS-17 further reduce the surface energy of the coating surface, making it more difficult for water to spread on the coating surface, thus greatly improving the hydrophobicity of the coating.
[0028] 4. Acrylic resin and polyurethane
[0029] Acrylic resin has good weather resistance, chemical resistance and adhesion, and can provide basic mechanical properties and chemical stability for the coating. Polyurethane has excellent flexibility and wear resistance, and can increase the elasticity and impact resistance of the coating. The composite resin formed by mixing the two serves as the matrix of the coating, provides a stable dispersion environment for other raw materials, and forms a continuous film structure after curing, firmly binding other raw materials together and endowing the coating with overall strength and stability.
[0030] 5. γ-aminopropyltriethoxysilane
[0031] γ-aminopropyltriethoxysilane is a coupling agent. One end of it contains ethoxy groups that can react with the surface of silica particles, and the other end contains amino groups that can react with acrylic resin and polyurethane. In this way, γ-aminopropyltriethoxysilane can establish a chemical bond connection between the inorganic silica particles and the organic resin matrix, enhance the interfacial bonding force between the inorganic phase and the organic phase, improve the comprehensive performance of the coating, and play an important role especially in improving the adhesion and water resistance of the coating.
[0032] 6. Cellulose nanocrystals (CNC)
[0033] Cellulose nanocrystals have high strength, high modulus and good biocompatibility. In the coating, CNC can play a role in strengthening and toughening. It can be dispersed in the resin matrix to form a nano-reinforced network structure, hinder the propagation of cracks, and improve the crack resistance of the coating. At the same time, CNC can also improve the rheological properties of the coating, which is beneficial to the uniform coating of the coating.
[0034] 7. Epoxy resin (EP)
[0035] Epoxy resin has excellent adhesion, chemical corrosion resistance and mechanical properties. In the coating, epoxy resin can undergo cross-linking reactions with acrylic resin, polyurethane and γ-aminopropyltriethoxysilane to form a more dense three-dimensional network structure, further improving the hardness, wear resistance and chemical corrosion resistance of the coating, and enhancing the structural stability of the coating.
[0036] II. Synergistic effect of raw materials
[0037] 1. Synergy between silica particles and FAS-17
[0038] Silica particles provide the micro-roughness of the coating surface, while FAS-17 reduces the surface energy of the coating surface. The synergistic effect of the two enables the coating surface to have both a suitable microstructure and an extremely low surface energy, thus achieving superhydrophobic performance. For example, the water contact angle of the silica particle coating without FAS-17 modification may be only about 120°, while after being modified with FAS-17, the water contact angle can be increased to more than 160°.
[0039] 2. Synergy between composite resin and modified silica particles
[0040] The composite resin composed of acrylic resin and polyurethane provides a good dispersion medium and bonding matrix for the modified silica particles. The modified silica particles are uniformly dispersed in the composite resin, which not only enhances the hydrophobicity of the coating, but also improves the strength and toughness of the coating. The bonding effect of the composite resin enables the silica particles to firmly adhere to the coating, avoiding the shedding of particles, thus ensuring the long-term stability and wear resistance of the coating.
[0041] 3. Bridging effect of γ-aminopropyltriethoxysilane
[0042] γ-aminopropyltriethoxysilane connects silica particles and composite resin through chemical bonds, enhancing the interfacial bonding force between the two. This connection enables the inorganic phase and the organic phase to work better together, improving the overall performance of the coating. For example, when subjected to external forces, due to the presence of γ-aminopropyltriethoxysilane, the stress can be better transmitted between the silica particles and the composite resin, reducing the cracking and peeling phenomena of the coating.
[0043] 4. Synergy between CNC and EP and other raw materials
[0044] The addition of CNC and EP further optimizes the performance of the coating. The nano-reinforced network structure of CNC is intertwined with the composite resin and silica particles, improving the crack resistance of the coating. The epoxy resin undergoes a cross-linking reaction with other raw materials, and the formed three-dimensional network structure tightly binds CNC, silica particles and the composite resin together, enhancing the hardness, wear resistance and structural stability of the coating.
[0045] III. Necessity and importance of process parameter control
[0046] 1. Ultrasonic cleaning time of glass slides (10 - 15 min)
[0047] If the ultrasonic cleaning time is too short, the oil stains and impurities on the surface of the glass slide may not be completely removed, which will affect the adhesion between the coating and the glass slide, resulting in the coating being prone to peeling during subsequent use. If the cleaning time is too long, it may cause damage to the surface of the glass slide, which is also not conducive to the adhesion and performance of the coating. After 10 - 15 minutes of ultrasonic cleaning, the surface of the glass slide can reach a clean and undamaged state, providing a good foundation for the coating, enabling the coating to adhere evenly and firmly to the glass slide.
[0048] 2. Stirring and ultrasonic dispersion time of silica particles
[0049] Stir for 15 minutes and then ultrasonic disperse for 10 - 15 minutes: The purpose of stirring is to initially disperse the silica particles in absolute ethanol to prepare for subsequent ultrasonic dispersion. If the stirring time is too short, the particles may not be fully dispersed, resulting in poor subsequent ultrasonic dispersion effect. Ultrasonic dispersion can further break the agglomeration of the particles and make the particles evenly dispersed in the solution. If the ultrasonic dispersion time is too short, the particles are not evenly dispersed, which will affect the uniformity of the surface roughness of the coating, and thus affect the hydrophobicity and other properties of the coating. If the ultrasonic time is too long, it may cause the particle size to become smaller and damage the original structure of the particles, which is also not conducive to the realization of the coating performance. Through optimized stirring and ultrasonic dispersion time, the silica particles can be evenly dispersed, providing good conditions for subsequent surface modification and coating preparation.
[0050] 3. Stirring temperature and time of composite resin
[0051] Stir for 1 hour under the water bath condition of 35 - 40 °C: Within this temperature and time range, the acrylic resin and polyurethane can be fully dissolved and mixed to form a uniform solution. If the temperature is too low, the dissolution rate of the resin is slow and the mixing is uneven, which will affect the performance of the coating. If the temperature is too high, it may cause partial cross-linking or degradation of the resin, which is also not conducive to the improvement of the coating performance. If the stirring time is too short, the resin is not fully mixed, resulting in unstable coating performance; if the stirring time is too long, it will not only waste time and energy, but also may introduce impurities or cause excessive evaporation of the solution. Stirring for 1 hour under the water bath condition of 35 - 40 °C can ensure the full mixing of the composite resin and provide a stable matrix for subsequent coating preparation.
[0052] 4. Stirring time (30 minutes) after adding modified silica
[0053] After adding the modified silica to the composite resin, it needs to be stirred for a certain period of time to ensure uniform dispersion. If the stirring time is too short, the silica particles may not be fully dispersed in the resin, resulting in uneven coating properties. If the stirring time is too long, the modified layer on the silica particles may be damaged, affecting the hydrophobicity of the coating. A stirring time of 30 minutes ensures that the modified silica particles are evenly dispersed in the composite resin, ensuring uniform and stable coating properties.
[0054] 5. Stirring time after adding γ-aminopropyltriethoxysilane, CNC and EP (30-35 minutes)
[0055] After adding γ-aminopropyltriethoxysilane, CNC, and EP, they need to be thoroughly stirred to allow them to fully react and mix with the composite resin and modified silica. γ-aminopropyltriethoxysilane requires time to chemically bond with the silica particles and resin, while CNC and EP also require time to interact with the other raw materials to form a stable structure. Too short a stirring time will result in inadequate reaction and mixing, affecting the overall performance of the coating. Too long a stirring time may cause the system to overreact or introduce defects such as unnecessary bubbles. A stirring time of 30-35 minutes ensures that all raw materials fully react and mix, forming a stable coating system.
[0056] 6. Room temperature curing time (10-15 minutes)
[0057] Room temperature curing time is crucial to the performance of a coating. If the curing time is too short, the coating may not fully cure, resulting in poor hardness, abrasion resistance, and water resistance. If the curing time is too long, cracks or other defects may form on the coating surface, affecting its appearance and performance. A room temperature curing time of 10-15 minutes allows the coating to fully cure, resulting in a superhydrophobic coating with excellent performance.
[0058] By optimizing the raw material dosages and process parameters, the resulting high-performance, water-based, acrylic-based super-hydrophobic coating for soft ceramic tiles exhibits exceptional overall performance. Its optimal average static water contact angle reaches 162.689°. It exhibits excellent resistance to acid and alkali solutions, high and low temperatures, abrasion resistance, and self-cleaning properties, making it suitable as a protective coating for outdoor decorative materials and possessing significant potential for application in the decorative field. This performance improvement, the result of the synergistic effect of the various raw materials and optimized process parameters, is an unexpected technical achievement.
[0059] The technical solution of the present invention has the following technical advantages compared with the prior art:
[0060] (1) The superhydrophobic coating material of the present invention is prepared by adding nano-scale silica particles modified with 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to the composite resin and adding γ-aminopropyltriethoxysilane. By controlling the addition amount, roughness and particle size of the nano-scale silica particles, the most suitable roughness and the best hydrophobic ability are found. The nano-scale silica particles can not only enhance the strength and toughness of the superhydrophobic coating material, but also endow the coating with high hydrophobicity and certain wear resistance. A superhydrophobic coating material with stable properties and certain wear resistance can be obtained. The introduction of CNC and EP improves the final crack resistance and structural stability of the coating.
[0061] (2) Nano-scale silica particles modified with 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane (FAS-17) were filled into the composite resin of aqueous acrylic acid (AA) and aqueous polyurethane (WPU) to prepare an aqueous acrylic polyurethane-SiO2 organic-inorganic interpenetrating network. X-ray photoelectron spectroscopy (XPS) can show that FAS-17 was successfully filled into SiO2. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) can both show that the synthesized coating has a uniform and neat mountain-valley structure, providing strong evidence for the superhydrophobic performance of the coating. The best average value of the static water contact angle is 162.689°. Tests on acid and alkali solutions resistance, high and low temperature environments resistance, wear resistance and self-cleaning can all prove that the prepared superhydrophobic coating material can be applied as a protective coating for outdoor decorative materials. The test results of the thermal analyzer show that the superhydrophobic coating material has good thermal properties. In summary, the comprehensive performance of the high-performance aqueous acrylic-based soft porcelain superhydrophobic coating material prepared by the present invention has great application potential in the decoration field. Description of the Drawings
[0062] Figure 1 is the experimental flow chart;
[0063] Figure 2 is the static contact angle results graph of water under different conditions (A is with KH550 as the variable, B is with SiO2 as the variable, C is with CNC as the variable, D is with EP as the variable);
[0064] Figure 3 is the graph of the mass wear of the superhydrophobic coating material prepared from resins with different ratios (A) and the comparison of the static contact angle of water before and after wear (B);
[0065] Figure 4 is the scanning electron microscopy graph of doped SiO2 with different masses (A is 0.25 g, B is 0.3 g, C is 0.35 g);
[0066] Figure 5Particle size (A) and Zeta potential (B) diagrams of superhydrophobic coating material A-W-0.24;
[0067] Figure 6 XPS diagrams of superhydrophobic coating material A-W-0.24 (A is the total spectrum of the spectral image, B is C1s, C is O1s);
[0068] Figure 7 AFM images of superhydrophobic coating material A-W-0.24 (A is the 3D image, B is the 2D image);
[0069] Figure 8 Diagrams of the change in the water contact angle of the superhydrophobic coating material A-W-0.24 under the influence of acid and alkali solutions (A), and the change in the water contact angle of the coating under the influence of high and low temperatures (B);
[0070] Figure 9 Diagram of the self-cleaning situation of superhydrophobic coating material A-W-0.24, where Figure 9 (A) Experimental diagram showing the superhydrophobicity of superhydrophobic coating material A-W-0.24, Figure 9 (B) Experimental diagram before simulating the coating covered with dust, Figure 9 (C) Experimental diagram after the dust is washed away with water flow, which can show the self-cleaning ability of the coating;
[0071] Figure 10 TG, DSC, and DTG diagrams of the thermal properties of superhydrophobic coating material A-W-0.24;
[0072] Figure 11 Diagram of the influence of different coating methods on the static water contact angle of superhydrophobic coating material A-W-0.24. Detailed implementation manners
[0073] The present invention will be further described in detail below in combination with the detailed implementation manners and with reference to the accompanying drawings. It should be emphasized that the following description is merely exemplary and not intended to limit the scope of the present invention and its applications.
[0074] 1. Experimental part
[0075] 1.1 Materials and reagents
[0076] Water-based acrylic resin. Cellulose nanocrystals. Water-based polyurethane (F0402), Shenzhen Jitian Chemical Co., Ltd. Anhydrous ethanol (analytical grade), Sinopharm Chemical Reagent Co., Ltd. Nanosilica (20 nm), Zhenhan New Materials (Suzhou) Co., Ltd. 1H,1H,2H,2H-perfluorodecyltriethoxysilane (96%, analytical grade), Shanghai MacLean Biochemical Technology Co., Ltd. Water-based epoxy resin emulsion, Shenyang Dongyan Paint Decoration Co., Ltd. γ-Aminopropyltriethoxysilane (98%, analytical grade), Shandong Keyuan Biochemical Co., Ltd. Deionized water (pure water, homemade). Sodium hydroxide (analytical grade), Shanghai MacLean Biochemical Technology Co., Ltd.
[0077] 1.2 Coating preparation (see Figure 1 )
[0078] (1) Preprocessing
[0079] Place the slide in a beaker of anhydrous ethanol and ultrasonically clean it for 10 minutes. Then, place the cleaned slide in an oven to dry it for later use.
[0080] Weigh 3 g of silica particles and place them in a 50 mL beaker. Then add 30 mL of anhydrous ethanol to the beaker, stir for 15 minutes, and disperse it in an ultrasonic vibration cleaner for 15 minutes to make it evenly dispersed. Then add 5 μL of FAS-17 dropwise to the beaker, place it in a 60°C water bath and stir until all the anhydrous ethanol is evaporated. Cool it to obtain the modified silica for use.
[0081] (2) Preparation of coating
[0082] As shown in Table 1, a certain proportion of water-based acrylic resin (AA), water-based polyurethane (WPU) and 10 mL of anhydrous ethanol were added to a 25 mL beaker and stirred in a water bath at 35°C for 1 hour. 0.3 g of modified silica was weighed and added to the beaker. After stirring in a water bath at 35°C for 30 minutes, 60 μL of γ-aminopropyltriethoxysilane (KH550), 10 μL of cellulose nanocrystals (CNC) and 10 μL of water-based epoxy resin (EP) were added. The mixture was stirred in a water bath at 35°C for 30 minutes and then cooled to room temperature.
[0083]
[0084] The coating was applied on a glass slide using different coating methods and cured at room temperature for 10 minutes to obtain a transparent super-hydrophobic coating material.
[0085] 1.3 Characterization methods
[0086] 1.3.1 Determination of contact angle
[0087] The static water contact angle of the emulsion coating on the glass plate was analyzed at 25 °C using a contact angle meter (SDC-350, CHN) by the sessile drop method. The average value of the angles obtained at more than 10 different positions on each sample surface was taken.
[0088] 1.3.2 Particle Size and Zeta Potential Measurement
[0089] The particle size and potential of the latex were analyzed by measuring the particle size of the high-solid emulsion diluted at least 50 times with deionized water on a nano particle size and Zeta potential analyzer (Malvern Zetasizer Nano ZS90, UK).
[0090] 1.3.3 Scanning Electron Microscopy Morphology Measurement
[0091] The surface and cross-sectional morphologies of the emulsion were studied using a scanning electron microscope (SEM) of Hitachi-S520 (Oxford link ISISSEM Model, JPN).
[0092] 1.3.4 Atomic Force Microscopy Measurement
[0093] The atomic force microscope (AFM, Bruker Nano Lnc, GER) was used to measure the surface roughness of the coating. The XYZ three-axis closed-loop scanner, 90 μm in the XY direction and 10 μm in the Z direction, can meet the requirements of atomic image testing.
[0094] 1.3.5 X-ray Photoelectron Spectroscopy Test
[0095] An X-ray photoelectron spectrometer (XPS, Thermo Fisher, USA) with an energy range of 0 - 5000 eV was used to measure the chemical composition or elemental composition of the coating.
[0096] 1.3.6 Adhesion Test
[0097] The wear resistance of the coating was tested by loading a 50 g weight on the coating and making a tangential uniform motion of 100 mm on 800-mesh sandpaper.
[0098] 1.3.7 Corrosion Resistance Test
[0099] The corrosion resistance of the coating was tested by soaking the coating in acid and alkali solutions. The coating was placed in HCl solution with pH = 5 and 5%wt NaOH solution, and soaked for 0 - 12 h respectively, and the change of the water contact angle of the coating with time was observed.
[0100] 1.3.8 Weather Resistance Test
[0101] The weather resistance of the coating is tested using high-temperature and low-temperature environments, and the temperature resistance of the coating is tested by standing at +100 °C and -20 °C for 0 - 10 days.
[0102] 1.3.9 Self-cleaning test
[0103] The self-cleaning property of the coating is tested by the ability of water droplets to drip on the superhydrophobic surface and carry away the pollutants on its surface.
[0104] 1.3.10 Test on the influence of different coating methods on the coating properties
[0105] Four coating methods, namely spraying method, spin coating method, dipping method and drop coating method, are used for coating, and the hydrophobic properties of the coating are tested to compare the influence of different coating methods on the coating properties.
[0106] 1.3.11 Thermal stability determination
[0107] Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) are used to analyze the thermal stability of the prepared emulsion by a thermal analyzer (Netzsch TG 209 F3, GER) and a differential scanning calorimeter (TAQ2000, DSC250, USA). The sample is heated from room temperature to 1000 °C at a heating rate of 10 °C / min under a nitrogen atmosphere.
[0108] 2 Results and discussion
[0109] 2.1 Results and discussion of single factors
[0110] The static water contact angle usually refers to the wetting degree of the solid surface. Generally, when the liquid stably exists on the solid surface, the contact angle between the liquid and the solid surface is measured. The size of the static contact angle θ is divided into the following types:
[0111] When θ < 5°, the liquid completely spreads on the solid surface, which is a superhydrophilic surface;
[0112] When 5° < θ ≤ 90°, the liquid partially spreads on the solid surface, which is a hydrophilic surface;
[0113] When 90° ≤ θ < 150°, a small part of the liquid surface spreads on the solid surface, which is a hydrophobic surface;
[0114] When 150° ≤ θ < 180°, the liquid is spherical on the solid surface, which is a superhydrophobic surface.
[0115] Figure 2is the static contact angle between the coating prepared under single-factor conditions and water. Figure A shows KH550 as the single-factor variable, Figure B shows SiO2 as the single-factor variable, Figure C shows CNC as the single-factor variable, and Figure D shows EP as the single-factor variable. The optimal process conditions for preparing the superhydrophobic coating material were obtained through single-factor experiments. The static water contact angle of the hydrophobic coating on the soft magnetic sheet prepared under the optimal process conditions was measured. After repeating three times, the average value was 162.689°, which is the optimal static water contact angle and is suitable for the superhydrophobic coating material on the surface of the soft magnetic sheet.
[0116] 2.2 Wear resistance of composite resins with different ratios
[0117] Figure 3 is a comparison chart of the mass wear of the superhydrophobic coating material prepared with resins of different ratios and the static contact angle with water before and after wear. A 50g weight was loaded on the coating, and the coating was placed on 800-mesh sandpaper and moved tangentially at a constant speed for 100 mm to obtain the mass wear. First, we can see through Figure 3 (A) that the mass wear of A-W-0.24 is the smallest, indicating that its wear resistance is the best. At the same time, through Figure 3 (B), it can be seen that the static water contact angle of A-W-0.24 reaches the maximum. This shows that the contact angle of the composite resin is deeply affected by the contents of AA and WPU. This is because the waterborne polyurethane surface has hydrophilic groups. As the hydrophilic groups are reduced to an appropriate degree, the hydrophobic performance of the composite coating reaches the best. And compared with the large decrease in the static water contact angle after friction of other composite resins with different ratios, the decrease in the static water contact angle of A-W-0.24 (that is, 0.24 g of waterborne acrylic resin AA, 0.96 g of waterborne polyurethane WPU, 0.3 g of FAS-17 modified silica SiO2, 60 μL of γ-aminopropyltriethoxysilane KH550, 10 μL of cellulose nanocrystal CNC, and 10 μL of waterborne epoxy resin EP) after friction is smaller, indicating that its wear resistance is the most excellent.
[0118] 2.3 Results of scanning electron microscopy analysis
[0119] As Figure 4There are obvious differences among the SEM images of different masses of doped SiO2. When the added mass of nanoscale silica is 0.25 g, the surface of the coating is basically covered by the composite resin. It seems that the amount of silica is less and the structure formed by the incomplete flat coverage does not provide enough roughness for the coating. When the added mass of nanoscale silica is 0.3 g, it can be clearly seen that the silica forms an uneven and undulating surface structure, and there are basically no obvious protrusions and depressions in terms of roughness. When the added mass of nanoscale silica is 0.35 g, it can be seen that the silica forms agglomerations and there are obvious protrusions, which is not conducive to the preparation of a superhydrophobic coating material with a flat surface. Generally speaking, when the added mass of nanoscale silica is 0.3 g, a morphological structure with a certain roughness formed by nanoscale silica and resin can be clearly seen, and the distribution of protrusions and depressions formed by the coating can be obviously seen to be uniform, so that the coating reaches the superhydrophobic state.
[0120] 2.4 Analysis Results of Particle Size and Zeta Potential
[0121] Figure 5 Figure showing the measurement results of the particle size and Zeta potential of the superhydrophobic coating material A-W-0.24. Particle size test results Figure 5 (A)It can be seen that the particle size of the emulsion is relatively appropriate. Zeta potential test results Figure 5 (B)It can be seen that the coating is very stable, both indicating the good stability of all emulsions.
[0122] 2.5 XPS Analysis Results
[0123] As Figure 6 shown, the surface groups and elemental content distribution of the superhydrophobic coating material A-W-0.24 were analyzed. From Figure 6 (A)It can be seen that obvious characteristic peaks of C1s, N1s, O1s, F1s and Si2p exist in the superhydrophobic coating material A-W-0.24. It can be seen that FAS-17 was successfully modified on the nanoscale SiO2, introducing a fluorine-containing long chain. Therefore Figure 6 (B)an obvious C-F peak appears in the spectrum. It is this low surface energy F that provides a good chemical basis for the superhydrophobicity of the coating. Combining with the roughness provided by the SiO2 particles, the composite coating has excellent superhydrophobic performance. Figure 6 (C)The Si-O in the spectrum indicates that silica was successfully incorporated into the composite coating, and the provided roughness also makes the composite coating have excellent superhydrophobic performance.
[0124] 2.6 AFM Images
[0125] Figure 7The surface of the superhydrophobic coating material A-W-0.24 was photographed by atomic force microscopy, which can more intuitively observe the roughness and distribution of the coating surface from a microscopic perspective. Figure 7 (A) is a 3D image of the superhydrophobic coating material A-W-0.24, from which it can be clearly seen that the coating surface has a rough structure and is evenly distributed. The raised areas are the peaks formed by particle agglomeration, and the depressions are filled with air, thus achieving a hydrophobic effect. Figure 7 (B) is a 2D image of the superhydrophobic coating material A-W-0.24. It can be very intuitively seen that the bright parts of the coating are the peaks formed by particle agglomeration, and the darker parts are the valleys formed by less particle distribution. It can also be seen that the distribution is relatively uniform.
[0126] 2.7 Acid and alkali resistance and temperature resistance
[0127] When the soft porcelain tile is used for outdoor building decoration, it will be affected by the changes in the natural environmental climate. The present invention simulates the natural environment to treat the superhydrophobic coating material A-W-0.24. The coating is soaked in acid and alkali solutions, as shown in Figure 8 (A). The coating is placed in HCl solution with pH = 5 and 5%wt NaOH solution, and the coating is soaked for 0 - 12h respectively; the coating is observed under high-temperature and low-temperature environments (standing at +100°C and -20°C for 0 - 10 days), as shown in Figure 8 (B).
[0128] As Figure 8 shown in (A), it can be clearly seen that when the alkali immersion exceeds 6h, the static water contact angle of the coating is lower than 90°. The alkali solution directly destroys the internal structure of the coating and turns the coating into a hydrophilic surface. When the coating is acid-soaked for 12h, the surface structure and chemical composition of the coating are further damaged by the acid, resulting in the loss of the superhydrophobic performance of the coating and becoming a hydrophobic state with a static water contact angle above 110°. Therefore, the acid resistance of the superhydrophobic coating material A-W-0.24 is much higher than its alkali resistance.
[0129] As Figure 8 shown in (B), although the water contact angle decreases under high-temperature conditions, it still remains above 150° for the first 6 days, indicating that the superhydrophobic coating material A-W-0.24 has strong high-temperature tolerance. When the coating is in a low-temperature environment, it also maintains a superhydrophobic angle above 150° for the first 4 days, indicating that the coating has a certain low-temperature tolerance within a certain period of time.
[0130] 2.8 Self-cleaning ability
[0131] In the natural environment, exterior wall decoration materials are prone to being contaminated by some dust and other pollutants. Therefore, black powder is used to simulate natural environmental pollutants to study the self-cleaning performance of the transparent superhydrophobic coating material A-W-0.24 against pollution. Figure 9 For the self-cleaning ability test experiment of the superhydrophobic coating material A-W-0.24, Figure 9 In the test experiment of (A), a micro syringe is used to squeeze the liquid water droplets to drop, contact the surface of the coating, and then control the needle to continue to move downward. It can be seen that the water droplets have completely contacted under the action of the needle force. Then, when the needle is controlled to move upward, it can be clearly seen that the water droplets are quickly lifted. Figure 9 (B) and Figure 9 In the test experiments of (C), when water droplets are dropped on the surface attached with dust, a water ball will be formed to carry away the dust, and finally a concave mark of a water droplet carrying away the dust will be formed on its surface.
[0132] 2.9 Thermal performance analysis results
[0133] Figure 10 For the TG, DTG, and DSC curves of the superhydrophobic coating material A-W-0.24, it can be clearly seen that on the TG / DTG curves, there is a main temperature range around 100 °C, indicating that the change in mass loss Δm1 is the evaporation of ethanol. When the temperature is around 900 - 1200 °C, an absorption peak of DSC is observed, indicating that the copolymer undergoes a phase change at this time. It can be known that the copolymer has good thermal stability, indicating that the superhydrophobic coating material A-W-0.24 has great application prospects in the field of outdoor decoration materials.
[0134] 2.10 Effects of different coating methods on the coating
[0135] Figure 11 The effects of four different coating processes, namely spraying, dipping, spin coating, and drop coating, on the coating are compared. Among these four processes, the static water contact angle of the coating prepared by the spraying process is the largest, and that of the drop coating method is the smallest. By analyzing the experimental process and test results, it can be known that in the dipping method, the coating cures slowly during the dipping process and fails to adhere completely, so the contact angle is the smallest and the error is relatively large; in the spraying method, the coating is too dense, resulting in an uneven and untidy mountain and valley structure, leading to poor hydrophobicity; the spin coating method has the smallest error and is the most stable coating method; the static water contact angle of the coating prepared by the drop coating method reaches the largest, but its error is relatively large and it is easily affected by the fluidity of the coating itself.
[0136] 3 Conclusions
[0137] In this study, superhydrophobic coating materials were prepared by adding nanoscale silica particles modified with 1H, 1H, 2H, 2H-perfluorodecyltriethoxysilane to the composite resin and adding γ-aminopropyltriethoxysilane. By controlling the addition amount, roughness, and particle size of the nanoscale silica particles, the most suitable roughness and the best hydrophobic ability were found. The introduction of CNC and EP improved the final crack resistance and structural stability of the coating.
[0138] The results obtained are as follows:
[0139] (1) The superhydrophobic coating material A-W-0.24 was the optimal process condition: 0.24 g of waterborne acrylic resin (AA), 0.96 g of waterborne polyurethane (WPU), 0.3 g of FAS-17 modified silica (SiO2), 60 μL of γ-aminopropyltriethoxysilane (KH550), 10 μL of cellulose nanocrystals (CNC), and 10 μL of waterborne epoxy resin (EP). The static water contact angle reached 162.689°.
[0140] (2) The scanning electron microscope results, particle size, and Zeta potential performance test results showed that the superhydrophobic coating material A-W-0.24 formed an uneven, uniform, and neat morphological structure.
[0141] (3) The XPS spectrum could show that when FAS-17 modified SiO2 was added to the composite resin, the low surface energy F provided a good chemical basis for the superhydrophobicity of the coating. Combining with the roughness provided by the SiO2 particles, the coating had excellent superhydrophobic performance.
[0142] (4) The temperature resistance and corrosion resistance results showed that the superhydrophobic coating material A-W-0.24 had good high and low temperature resistance, acid corrosion resistance, and the alkali corrosion resistance still needed to be further improved. The self-cleaning results showed that the superhydrophobic coating material A-W-0.24 had good self-cleaning properties.
[0143] From the TG, DTG, and DSC curves of the superhydrophobic coating material A-W-0.24, it had good thermal stability, indicating that the superhydrophobic coating material A-W-0.24 had a wider application prospect as an outdoor decorative material coating.
Claims
1. A preparation method of a high-performance waterborne acrylic-based soft porcelain chip superhydrophobic coating material, characterized in that, It includes the following steps: (1) Put the glass slide into a beaker containing absolute ethanol for ultrasonic cleaning, and then put the cleaned glass slide into an oven for drying for later use; (2) Place the silica particles in a beaker, add absolute ethanol to the beaker, stir, and then place it in an ultrasonic vibration cleaning machine to disperse them evenly. Then, add FAS-17 dropwise to the beaker, put it in a water bath and stir until all the absolute ethanol has evaporated, and then cool to obtain the modified silica for standby; (3) Add acrylic resin, polyurethane, and absolute ethanol to a beaker, and then stir under water bath conditions. Add the modified silica to the beaker, then stir under water bath conditions, and then add γ-aminopropyltriethoxysilane, cellulose nanocrystals, and epoxy resin to it. Then, stir under water bath conditions and cool to room temperature; (4) Coat the coating on the glass slide by coating method, and obtain a high-performance waterborne acrylic-based soft porcelain superhydrophobic coating material after curing at room temperature.
2. The preparation method of a high-performance waterborne acrylic-based soft porcelain chip superhydrophobic coating material according to claim 1, characterized in that, In step (1), the time for putting the glass slide into the beaker containing absolute ethanol for ultrasonic cleaning is 10 - 15 min.
3. The preparation method of a high-performance waterborne acrylic-based soft porcelain sheet superhydrophobic coating material according to claim 1, characterized in that, In step (2), stir for 15 min and then place it in an ultrasonic vibration cleaning machine.
4. The preparation method of a high-performance waterborne acrylic-based soft porcelain sheet superhydrophobic coating material according to claim 1, characterized in that, In step (2), after stirring, place it in an ultrasonic vibration cleaning machine and disperse for 10 - 15 min to make it evenly dispersed.
5. The preparation method of a high-performance waterborne acrylic-based soft porcelain sheet superhydrophobic coating material according to claim 1, characterized in that, In step (3), add acrylic resin, polyurethane, and absolute ethanol to the beaker, and stir under water bath conditions at 35 - 40 °C for 1 h.
6. The preparation method of a high-performance waterborne acrylic-based soft porcelain chip superhydrophobic coating material according to claim 1, characterized in that In step (3), add the modified silica to the beaker, and stir under water bath conditions at 35 - 40 °C for 30 min.
7. The preparation method of a high-performance waterborne acrylic-based soft porcelain chip superhydrophobic coating material according to claim 1, characterized in that, In step (3), add γ-aminopropyltriethoxysilane, cellulose nanocrystals, and epoxy resin to it, stir under water bath conditions at 35 - 40 °C for 30 - 35 min, and then cool to room temperature.
8. The preparation method of a high-performance waterborne acrylic-based soft porcelain chip superhydrophobic coating material according to claim 1, characterized in that, In step (4), the curing time at room temperature is 10 - 15 min.
Citation Information
Patent Citations
Preparation method of zinc oxide and cellulose nanocrystal composite super-hydrophobic coating
CN105670500A
Durable super-hydrophobic three-proofing coating, and preparation method and use method thereof
CN111019456A
Preparation method of super-hydrophobic and oleophobic coating
CN114773997A
Preparation method of fluorocarbon resin / polycaprolactone-based self-healing super-hydrophobic coating
CN115502068A